Effects of Pimobendan on Prolonging Time to Rehospitalization or Frequency of Rehospitalization in Patients with Heart Failure: A Retrospective Cohort Study Using a Medical Administrative Database (PREFER Study) - Kazuhisa Kodama; Tatsunori Murata; Naoki Dohi; Masaaki Nakano; Toshiaki Yokoi; Tomohiro Sakamoto; Koichi Nakao (Journal of Health Economics and Outcomes Research)
**Background:** As approximately 24% of patients with chronic heart failure are rehospitalized within 1 year and heart failure is aggravated by repeated hospitalizations, greater importance was attached to the prevention of hospitalization.